(untitled) (Medical Forum Monthly, 2023)
ABSTRACT Objective: To determine the outcome of supine PCNL in patients with renal calculi with a previous history of renal surgery. Study Design: Retrospective clinical study Place and Duration of Study: This study was conducted at the Sami. Medical Centre. Abbottabad from April 2015 to December 2021. Materials and Methods: Forty-one patients with prior renal surgery received supine PCNL with spinal anesthesia (SA). The outcome included operation time, hospital stay, stone clearance rate, and surgical and SA-related complications. Results: Out of 41 patients, 70.7% were men. The mean age was 44.04±9.73 SD years, and the calculus size was 2.12±0.29 mm. The majority of the stones (61%) were single. Nephrolithotomy was previously performed in 80.5% of patients, followed by laparoscopic or endoscopic surgery in 12.2%, and partial nephrectomy in 7.3% of the patients. The mean operation time was 104 minutes, 30 hours was the mean hospital stay, and 84% was the stone clearance rate. Complications included fever (12.2%) and blood transfusions (4.6%). Headaches (4.6%), and backaches (4.6%), were caused by spinal anesthesia. Conclusion: Supine PCNL under spinal anesthesia is a safe and effective therapeutic option for patients with previous open nephrolithotomy. The procedure also requires minimal analgesia and has few postoperative problems.